PEMBINAAN ETOS KERJA GURU DAN KARYAWAN SEKOLAH DI BAWAH YAYASAN LI ULIL ALBAB KARANGANYAR - Wahyudi, Amin (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2018)
Yayasan Li Ulil Albab is one of the foundations in Karanganyar Regency that keep growing and contribute in educating the nation's life as well as building the character of the next generation of intelligent, religious by managing. To be able to carry out this noble task, it is necessary to continuously improve the work ethic of teachers and employees as an important element in improving the quality and achievement of school. Based on these considerations, lectures, counseling and various activities for coaching in order to improve the work ethic of teachers and employees is important to do. This event is attended by 46 Teachers and School Workers under Yayasan Li Ulil Albab Karanganyar. The purpose of this activity is that the work ethic of teachers and employees of schools under Yayasan Li Ulil Albab Karanganyar can be improved, and maintained, so that teachers and employees will be motivated in working, discipline, always positively to the task and work and able to build good cooperation with fellow teachers and employees to realize the process of learning and teaching is good and able to produce graduates qualified and character. This activity is expected to provide benefits to various stakeholders of the school under Yayasan Li Ulil Albab Karanganyar, namely: First, for teachers and employees, this activity is useful to provide enlightenment and motivation so that it will increase the work ethic in carrying out its duties. Second, for the students, this activity will provide indirect benefits to the students, because with the work ethic of teachers and employees of high students will get a better service of teaching and learning process. Third, for the Yayasan Li Ulil Albab Karanganyar, this activity will provide indirect benefits on improving the quality of the institution because it is supported by teachers and employees who have a good work ethic. The result of this coaching activity is the increasing work ethic of teachers and school employees under Yayasan Li Ulil Albab Karanganyar with an indicator of increasing morale, and discipline of teachers and employees in teaching and providing services to students that impact on student's learning achievement.Keywords: work ethic, teacher discipline, service to students